Kaidah Fikih Al-Darāhim wa Al-Danānīr Lā Tuʿayyan bi Al-Taʿyīn Fī ʿuqūd Al-Muʿāwaḍāt dan Implikasinya Terhadap Transaksi Keuangan Syariah Kontemporer: The Rules of Fikih Al-Darāhim wa Al-Danānīr Lā Tuʿayyan bi Al-Taʿyīn Fī ʿuqūd al-Muʿāwaḍāt and Its Implications for Contemporary Sharia Financial Transactions - Muhammad Dzaky Zainuri; Sopiallah Sopiallah; Lalu Ahmad Naufal Amrillah; Muhammad Louis Nawafil (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
The transformation of modern monetary systems, marked by the dominance of fiat money and the digitalization of financial transactions, raises significant conceptual challenges within Islamic law, particularly concerning the legal status of money in Islamic jurisprudence (fiqh al-muʿāmalāt). This study aims to analyze the conceptual construction of the legal maxim al-darāhim wa al-danānīr lā tuʿayyan bi al-taʿyīn in classical fiqh literature, examine its classification within the framework of Islamic legal maxims, and evaluate its relevance and implications for contemporary Islamic financial practices. This research employs a library-based method with a normative-conceptual approach, utilizing descriptive-analytical analysis of classical sources, contemporary scholarly works, and Islamic economic studies. The findings reveal that the maxim constitutes a qawāʿid far‘iyyah emphasizing the representative nature of money as tsaman (medium of exchange), rather than as a materially specified commodity. In the modern context, the maxim provides a conceptual basis for recognizing fiat money, electronic money, and digital financial instruments as valid forms of exchange, provided they fulfill their economic functions and gain social acceptance. The study also demonstrates that the claim prohibiting the trade of money is an oversimplification, as Islamic law recognizes bayʿ al-ṣarf under specific conditions. The main contribution of this study lies in reconstructing the maxim as an operational analytical framework that integrates classical jurisprudence, maqāṣid al-sharīʿah, and contemporary financial realities.